Development and evaluation of patient information leaflet for liver cirrhosis patients - Siddheesh Rajpurohit; Balaji Musunuri; Pooja Basthi Mohan; Lakshmi R. Vani; Ganesh Bhat; Shiran Shetty (Elsevier, 2023)
Problem considered: The present study aimed at developing and validating patient information leaflet (PIL) for liver cirrhosis patients. Methodology: PIL was prepared using canvas (an online design graphic tool). Up-to-date and Micromedex were used to gather information on liver cirrhosis. Before user testing, PIL readability was assessed by using the Flesch Reading Ease Score (FR-ES). Additionally, user opinion on the legibility and content of the PIL was also determined. Baker Able Leaflet Design (BALD) method was employed to assess the layout and design characteristics of the PIL. Results: A total of 52 participants with liver cirrhosis with a mean age of 53.04 ± 11.89 were enrolled in the study. A score of 22.2 was achieved for Flesch Reading Ease Score (FR-ES). The BALD scores for English and Kannada PIL were 25 and 23, respectively. User testing showed significant improvement (p-value: <0.05) in disease knowledge from 12 (6-20) to 16 (12-22). Spearman's correlation showed the disease duration as a significant factor affecting disease knowledge (rs:0.498; p-value: <0.001). Concerning user opinion, 48.1% (n,25) of patients reported the legibility and content of PIL as good. Conclusion: PIL met the standard criteria of readability and layout design. Pictogram-based PIL was found to be an effective patient education tool in improving patient disease knowledge in liver cirrhosis patients.